A scrum-inspired process for software product lines scoping - SILVA, Ivonei Freitas da (2013)
Scoping in Software Product Lines (SPL) is the first step to identify products, features, and assets in a market segment. Traditional approaches for SPL scoping are heavyweight and upfront processes in scenarios with unpredictable changes and little resources. An incurred key challenge is handling systematically the iterativeness, adaptability, and feedback in the SPL scoping process. As a final consequence, the software industry can hamper investment in the SPL scoping. In this context, the Scrum framework, as the most popular agile approach to foster the iterativeness, adaptability, and feedbacks, can address that challenge. Previous studies have combined Scrum into some SPL activities with good results. This thesis provides a process, named of RiPLE-SCA, for SPL scoping inspired in the Scrum practices. This process bases on industrial evidence (a case study of a traditional SPL scoping), expert opinion on agile SPL (through a survey), and scientific literature about agile SPL (a systematic mapping). A feasibility study and a cross-case study carried out with two industrial partners indicated that the RiPLE-SCA is practicable and appropriate for an industrial setting as well as fosters iterativeness, adaptability, and feedbacks detecting early obsolete features and changes in domain, requirements, features, and technology.